A New Characterization of Quasi-Analytic Classes of C(∞)-Functions - Darst, R. B. (Proc Natl Acad Sci U S A, 1972)
It is shown that a basic class C{M(n)} of C(∞)-functions contains only quasi-analytic functions if, and only if, every function in C{M(n)} maps Borel sets onto Borel sets.